Implementation of Blue Ocean Strategy (BOS) at the Opening of the UNINDRA PGRI Digital Business Department - Tri Angkarini; Rais Hidayat (International Journal of Research in Education, 2024)
The decreasing number of student admissions, especially when the Covid-19 pandemic hit and the increasing number of universities in Jakarta, the competition is getting tighter. For this reason, implementing the Blue Ocean Strategy by opening a Digital Business major is the right way to get out of the competition and find new, unexplored opportunities and markets. The aim of this research is to describe the process of implementing BOS at the opening of the Digital Business major. The method used in this research is a qualitative approach using interviews, observation and documentation studies as data collection techniques. The research results show that the formulation of the blue ocean strategy is going well, especially the decision to open a Digital Business major through the stages of market boundary reconstruction, ERRC scheme, 3 non-consumer levels and strategic series. This is proven by the number of students who choose this major amounting to approximately 300 people with a class size of 10. Relevant curriculum development, industrial collaboration, use of technology in learning, lecturer training and effective promotion are suggestions that should be considered for the success of this implementation in long-term